COMMUNICATION POLITICS AND DEMOCRACY DIALOGUE: : CASE STUDY ON THE INDONESIAN PRESIDENTIAL ELECTION 2024 - Aditya, Krisna Krisna; Bintang, Gilang (UKRI, 2024)
This article discusses the analysis of political communication and democratic dialogue in Indonesia as the largest democratic country which is currently carrying out a democratic process in the 2024 legislative and presidential elections. Another thing in various case studies in Indonesia highlights the principle problems in democracy. Election process, money politics, elite pragmatism, institutional weaknesses of political parties. The article also mentions the important role of dialogue in political communication and the potential for spreading misinformation and tending to attack political figures. Research shows that there is a tendency for democratic decline which has an impact on weakening the integrity of the electoral process. This reflects democracy which is still problematic in various aspects, starting from civil liberties, government functions, to the election process. As we know, several factors causing the decline of democracy include the growth of digital politics, populism, the economic transformation of society, and the impact of the pandemic. Talking about democracy today, as we have observed, many problems occur in the world because of stagnant dialogue due to broken bridges between civilizations. Dialogue and discussion efforts are one of the efforts to build a healthy democratic country. There is not a single democratic principle in the world that is perfect. In fact, until now democracy is still developing. The development of democracy in Indonesia continues to experience changes as a form of search for national identity which is marked by several failures. It was also stated that the various difficulties that befell Indonesia, ranging from the financial and monetary crisis to conflicts of interest, actually perfected democracy because society became more united and stronger. Indonesian democracy runs side by side with the largest number of Muslims and modernization. Democracy in Indonesia has its own characteristics. Therefore, democratization never stops. Talking about democracy will always be relevant.